The Chest Expansion Values among Adult Healthy Iraqi People (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: the measurements of chest  expansion    are  performed  to  appreciate   a patient’s treatment  efficacy, standard  status,  and  evolution  of disease  in relation  to respiratory  muscle function and chest  wall  mobility  .Methods:  In this study random collection of  1020  persons  (530  male  and 490 female)  aged  between  20  to 70  years  old  from  Baghdad  and  Al-Najaf  city,  Participants  have no history of orthopedic, neurological, rheumatologic  or  respiratory  diseases , the  smokers  were  excluded from this study.The chest expansion measured in 2 sites, the first site is the upper thoracic excursion, at the level of the fifth thoracic spinous process and the third intercostal space at the mid clavicular line. The second site is the lower thoracic excursion, the tape measure was placed at the level of the 10th thoracic spinous process and the tip of the xiphoid process by using tape measure.Results: The men group shows a significant larger chest  expansion  than  women group  in  upper  thorax  (5±0.6cm, 4.2±0.7cm)  for  men  and  women  respectively  and  at the chest expansion in the lower  thorax (4.5±0.6cm, 3.7±0.6cm) for  men and  women  respectively (p